(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This article examines the theoretical foundations and practical applications of lexical transformations in translation studies. It analyses the semantic mechanisms behind concretization, generalization, contextual substitution, antonymic translation, and compensation, with a particular focus on their role in preserving equivalence and ensuring naturalness in translated texts. Using examples from English and Uzbek, the article highlights how these transformations contribute to accuracy, clarity, and stylistic adequacy in translation practice.